Substance Over Form vs Authentic Deed: Liability and Legal Certainty for VAT Transfer of Land - Wijara Yasa, I Made Rai; Ida Ayu Sadnyini, Ida Ayu Sadnyini (Jurnal Ius Constituendum, 2025)
This study analyzes the legal implications of applying the substance over form principle in VAT imposition on land transfer transactions vis-a-vis authentic deeds, aiming to assess the legal liability and legal certainty. The urgency of this research is that the rise of formal transactions that obscure the economic substance of land transfer has challenged the effectiveness of VAT enforcement in Indonesia. The approach used in this research is a normative legal approach, which analyzes related regulations and literature documents. The research results concluded that legal responsibility for authentic deeds that do not fulfill the substance over form principle in the imposition of VAT depends on the condition of who violates the lawful cause clause in making the deed, so that legal responsibility can be borne by the PPAT and/or the parties. The principle of substance over form is only regulated in income tax regulations. In civil law, this principle is not regulated and explained, but with this principle, it can be proven that an authentic deed was made without a lawful cause as per Article 1320 of the Civil Code. Substance over form can give rise to new legal consequences for PPAT or parties in the transaction, even though it is not explicitly regulated in VAT regulations. This study is one of the few legal studies that highlights the gap between the practice of imposing VAT and the authenticity of PPAT deeds in the context of the substance over form principle.